Infrared refraction spectroscopy - Kramers-Kronig analysis revisited - Mayerhoefer, Thomas G.; Ivanovski, Vladimir; Popp, Juergen (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2022)
Since about 60 years, it is possible to determine the set of optical constants from reflectance measurements by the Kramers-Kronig relations. Unfortunately, the potential of the method seems to be limited in practice by the need to extend measured data into unknown regions by extrapolation, which is prone to error and leads to deviations from the true values in the known region depending on the method of extension. With the advent of infrared refraction spectroscopy, which uses reflectance measurements at normal or near normal incidence, the development of a fast method to determine the complex index of refraction function reliably for these cases has become an even more interesting goal. In this work, we introduce a way to perform a Kramers-Kronig analysis of such reflectance spectra without the need to extrapolate the measured data for higher wavenumbers beyond the measurement range. Furthermore, we introduce and compare very simple and reliable material-independent ways to extrapolate the measured data for lower wavenumbers. As a result, we devise fast and sufficiently accurate methods, which are easily implementable into existing spectrometer software, to extract quantitative spectral information from reflectance measurements at near normal incidence.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Kramers-Kronig relations; Reflection spectroscopy; Refraction spectroscopy